The Mediation Effect of Body Composition on the Association Between Menopause and Hyperuricemia: Evidence From China National Health Survey - He, Huijing; Pan, Li; Liu, Feng; Ren, Xiaolan; Cui, Ze; Pa, Lize; Zhao, Jingbo; Wang, Dingming; Du, Jianwei; Wang, Hailing; Wang, Xianghua; Peng, Xia; et al. (Frontiers in Endocrinology, 2022)
Reproductive factors have been demonstrated to be associated with hyperuricemia. Body composition is an essential determinant influencing serum uric acid (SUA), but it is largely unknown whether hyperuricemia results from reproductive factors, or the mediated effect caused by changed body composition during the menopausal transition. As a secondary analysis of China National Health Survey from 2012-2017, this study included 18997 women aged 20-80. Menarche age and menopause information was collected by self-report. Body mass index (BMI), body fat percentage (BFP), fat mass index (FMI) and fat free mass index (FFMI) were used as body composition indexes. Hyperuricemia was defined as SUA higher than 360μmol/L. Mediation analysis was performed to explore the direct and indirect effect of menopause on hyperuricemia. A 1:2 age-matched case-control data set (n=6202) was designed to control age-related confounders and was used in multivariable analyses. After adjusting for covariates, menopausal women had 14.08 (10.89-17.27) mol/L higher SUA than their pre-menopausal counterparts. Overweight/obesity, higher level of BFP, FMI and FFMI were all found to be positively associated with hyperuricemia. The mediation analysis showed that, the total effect of menopause on hyperuricemia was positive, but was substantially mediated by body composition indexes. 45% of the total effect can be attribute to the indirect effect mediated by BMI (OR for the natural indirect effect (NIE): 1.09, 95%CI: 1.04-1.13), and over 80% mediated by BFP (OR for NIE: 1.23, 95%CI: 1.16-1.29). However, FFMI did not present the mediated role in the association (OR for NIE: 0.99, 95%CI: 0.96-1.02). This study concluded that body composition, especially the fat mass indexes, significantly mediated the association between menopause and hyperuricemia. The role of body composition as mediators constitutes clinical and public health significance that should be recognized and considered in healthcare for pre-and post-menopausal women.